The Effect Of Antioxidants Addition On The Characteristics Of Palm Oil Base Food Grade Grease - erminawati, Erminawati; Yanto, Tri; Naufalin, Rifda (Jurnal Teknologi Pertanian, 2013)
Palm oil has been reported in many studies to be  potential as main ingredient for food grade grease base oil, but it  has  lower oxidative stability as compared to mineral oil. The addition of antioxidants can delay the oxidation reaction on food grade grease. This research aimed to study the effect of different type of antioxidant (TBHQ, BHT, combination of TBHQ and BHT) and different concentration of antioxidant (0, 0.1, 0.2, 0.3, 0.4, and 0.5%) on food grade grease characteristics. Several physychochemical variables such asoxidative defect test, melting point, pH and texture were observed. The results showed that different antioxidant  caused the differences on melting points; and different  antioxidant concentrations caused the differences on melting points and textures. According to zero-one analysis, the best performance was obtained from food grade grease formulated with combination of tert-butyl hydroquinoneand butylated hydroxytolueneantioxidant at 0.3% concentration. This food grade grease had specific characteristics as follow: 1a level of oxidative resistance; 125 °C of melting point; 7 of pH and 5.8 mm/s (NLGI 2) of texture. Keywords: food grade grease, palm oil, tert-butyl hydroquinone, butylated hydroxytoluene